Positive gender congruency effects on shopper responses: Field evidence from a gender egalitarian culture. (November 2021) - Otterbring, Tobias; Bhatnagar, Roopali; Samuelsson, Peter; Borau, Sylvie
Abstract: This field study examined how customer-employee interactions are affected by the congruency between an employee's gender and the perceived gender image of the consumption context in one of the most gender equal cultures in the world (Scandinavia). Mystery shoppers had a service encounter with an employee across a set of physical commercial settings that were classified according to their gender image. The mystery shoppers noted the gender of the employee, provided employee evaluations, and indicated word-of-mouth (WOM) ratings. Shoppers who had a gender congruent service encounter (e.g., a female employee in a "feminine" consumption context) reported more favorable employee evaluations and WOM ratings than shoppers who had a gender incongruent service encounter (e.g., a female employee in a "masculine" consumption context), with the impact of gender congruency on WOM ratings mediated by employee evaluations, particularly with respect to competence inferences. These findings highlight the ethical dilemma of a positive gender congruency effect, as it can generate superior consumer responses but also risks resulting in gender occupational segregation. Highlights: Gender congruent service encounters result in more favorable employee evaluations. Gender congruent service encounters result in more favorable WOM ratings. Employee evaluations mediate the gender congruency-WOM link. These results highlight the ethical dilemma of a positive gender congruency effect.